2019
DOI: 10.3389/fonc.2019.00189
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression Is Associated With VEGFA and LADC Patients' Survival

Abstract: Objectives: To elucidate the relationship between VEGFA and PD-L1 expression in lung adenocarcinoma (LADC). Methods: PD-L1 and VEGFA expression were determined by immunohistochemistry with H-score on formalin-fixed paraffin-embedded resected LADC specimens of 129 cases. Results: High PD-L1 expression in 53 (41.1%) patients, high VEGFA expression in 65 (50.4%), and co-expression in 18 (14.0%) were observed. Inverse correlation between expression of PD-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…HIF-1α and VEGFA expression were scored by the H-score system, respectively. H score calculation method is based on previous literature 15 .…”
Section: Evaluation Of the Percent Of Pd-l1 + Blood Vessels And The Pmentioning
confidence: 99%
“…HIF-1α and VEGFA expression were scored by the H-score system, respectively. H score calculation method is based on previous literature 15 .…”
Section: Evaluation Of the Percent Of Pd-l1 + Blood Vessels And The Pmentioning
confidence: 99%
“…VEGFA, an important member of vascular endothelial growth factor signaling pathway, mediates the tumoral angiogenesis, and results in the progression and metastasis of NSCLC (41,42). Besides, Liu et al (43) demonstrated that the co-expression of VEGFA and PD-L1 exhibited a worst overall survival in patients with resected LUAD, indicating the potential complicated interaction between VEGFA expression and immune checkpoint inhibitor therapy. The critical role TGFβ/BMP signaling pathway played in tumor cell growth, stemness, epithelial-mesenchymal transition, invasion, and migration in triple-negative breast cancer has also been published (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…H‐score > 100 was identified as a VEGFC high expression case. According to previous studies, PD‐L1 cutoff value was set at 100, ie. H‐score >100 was considered to be a PD‐L1 high expression case.…”
Section: Methodsmentioning
confidence: 99%